Construction and verification of hemi-anechoic room - Sodsri, Chukiet (Engineering and Applied Science Research, 2014)
Anechoic rooms for acoustical measurements and research studies, must have properties of being free field, capable of soundproof and have low background noise. Due to their thick and heavy walls, they are usually constructed on ground floor or structures specially designed to handle the weight. Modification of an existing empty room on an upper floor of a high building to be an anechoic room is therefore very challenging, since it could destroy the building structure. This paper presents construction and verification of a hemi-anechoic room, built on the 5th floor of a nine story building. Composited walls consisting of wooden and gypsum, stuffed with sound-absorptive materials, metal sheets, and air cavities, were designed. Walls’ surfaces were covered with linear wedge structures of fiberglass. Performance of the room was tested based on theory of spherical wave motion in free field. Result displayed that the constructed hemi-anechoic room has 300 Hz frequency cutoff and 22 dBA background noise level. The room sufficiently provides free field environment for being used in acoustical measurements and acoustic research study.